Thugs rje chen po ṅan soṅ raṅ grol las phyi sgrub daṅ ʼbrel baʼi phrin las bklags chog tu bkod pa pad dkar rgyas paʼi ʼdrum zer ces bya ba bźugs so - Koṅ-sprul Blo-gros-mthaʼ-yas, 1813-1899 (s.n., 1972)
Liturgical arrangement of rediscovered teachings from the Thugs rje chen po ṅan soṅ raṅ grol cycle of ʼJaʼ-tshon-sñiṅ-po, 1585-1656, concerned with the propitiation of a form of Avalokiteshvara.